2020
DOI: 10.1108/jamr-10-2019-0193
|View full text |Cite
|
Sign up to set email alerts
|

Parametric review of food supply chain performance implications under different aspects

Abstract: PurposePresented work gives comparative review of food supply chain (FSC) under various notions related to its conceptualisation, operationality and technological advancements in lieu with Industry 4.0 revolution. In Indian scenario, the impression of FSC seems in a scattered way that cannot be directly useful for an organisation, to overcome this scattering, a framework has been developed to consolidate the previous research works and exploration of new trends in food supply chain management (FSCM) in context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 143 publications
0
34
0
Order By: Relevance
“…Using spectral analysis technology, by observing the canopy spectral reflectance of hydroponic potted rice with different potassium nutrient levels, scholars found that the effect of potassium on the spectral characteristics of the canopy is similar to the effect of nitrogen. e spectral reflectance is reduced, and the spectral reflectance of the near-infrared band is significantly increased [25]. Some researchers believe that Monte Carlo simulation and diffuse reflectance spectroscopy can be used to establish a tomato nutrient supply model and analyze the intrinsic relationship between nutrient elements and near-infrared spectroscopy [26].…”
Section: Introductionmentioning
confidence: 99%
“…Using spectral analysis technology, by observing the canopy spectral reflectance of hydroponic potted rice with different potassium nutrient levels, scholars found that the effect of potassium on the spectral characteristics of the canopy is similar to the effect of nitrogen. e spectral reflectance is reduced, and the spectral reflectance of the near-infrared band is significantly increased [25]. Some researchers believe that Monte Carlo simulation and diffuse reflectance spectroscopy can be used to establish a tomato nutrient supply model and analyze the intrinsic relationship between nutrient elements and near-infrared spectroscopy [26].…”
Section: Introductionmentioning
confidence: 99%
“…The aspect of food processing and food collaborations between India and Britain was discussed with the help of a systematic literature survey (Gyan Prakash, 2018). The perusal of literature surveys of food supply chain performance will indicate future directions for food processing prospects and collaboration (Sharma et al , 2020). The literature survey over food waste scenario highlights the need for farmer skills, environmental awareness, utility of supply chain networks, stakeholder coordination, improved retail, consumer attitude and waste disposal (Rosenlund et al , 2020).…”
Section: Review Methodologymentioning
confidence: 99%
“…Loss management study has provided some key loss mitigation dynamics to be focused upon. The below-mentioned strategic loss mitigation dynamics obtained from the study are mentioned below:Adaptation and practice of value addition (APVA) (improved food processing) for produces and vertical integration (Yazdanparast et al , 2010; Rais and Sheoran, 2015; Hernández-Rubio et al ., 2016; Priyadarshi et al , 2019a; Calegari et al , 2020; Sharma et al , 2020). Improved quality (IPQL) (de Keizer et al , 2015).…”
Section: Critical Analysis Of Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…If the present industry is serving to kings, the industry of the future has to serve dictators. Though vast and growing literature (Kumar et al , 2020b; Machado et al , 2019; Ghobakhloo, 2018; Klingenberg et al , 2019; Nosalska et al , 2019; Wagire et al , 2019; Li et al , 2019; Shahin et al , 2020; Sharma et al , 2020; Rossini et al , 2019; Cohen et al , 2019) is available on I4.0, efforts are made to capture theSalient features of I4.0 and presented in Figure 1Essence of I4.0 and presented in following italic lines…”
Section: Introductionmentioning
confidence: 99%